Sulfidation failure of UMCo-50 protective sheath tube used for a temperature monitoring device exposed to sulfur dioxide bearing hot gas. (August 2022) - Ouampan, Siriwan; Kaewkumsai, Siam; Viyanit, Ekkarut
Highlights: The UMCo-50 protective sheath tube was severely damaged after 6 months in service. Sulfidation attack of UMCo-50 alloy was dealing with SO2 -bearing hot gas in service. Sulfidation resistance of the alloy was decreased by the undesired Cr-rich carbides. Temp fluctuation in 550 to 1100 °C was a key factor causing the carbide formation. Underneath sulfide scales, sulfidation attack was occurred along Cr-depleted zones. Abstract: The failure investigation of a thermocouple protective sheath tube made of UMCo-50 cobalt base alloy exposed to SO2 -bearing hot gas in a sulfur refining furnace was systematically conducted. Various microstructural examination techniques were employed in order to clarify a root cause of failure. A tip portion of protective sheath tube remarkably revealed its severe material degradation after exposure to SO2 -bearing hot gas in service for approximately 6 months. From the investigation, it turned out that the alloy was significantly prone to sulfidation attacks due to the formation of undesired chromium-rich carbides in its structure, which was accelerated by temperature fluctuation between 550 and 1100 °C during service. As a result, the protective sheath tube could not last for approximately 3 years as its design life.